3D interconnected porous graphene sheets loaded with cobalt oxide nanoparticles for lithium-ion battery anodes - Puthusseri, Dhanya; Aravindan, Vanchiappan; Madhavi, Srinivasan; Ogale, Satishchandra (Energy Technology, 2016)
Nanomaterials with high surface-to-volume ratio and tunable electronic and optical properties have expanded their use in variety of applications, especially energy conversion and storage. Here we report on the synthesis of a cobalt oxide (Co3O4)/3D-interconnected porous graphene (PG) nanocomposite by using a simple solvothermal route and its application as a Li-ion battery anode. Among the different compositions investigated, the composite PG-600 (with 50% PG) showed a discharge capacity of 700mAhg(-1) at a current density of 500mAg(-1) and maintained 90% retention after 80cycles. The high surface area of the 3DPG sheets helps the Co3O4 nanoparticles to form a uniform dispersion on the surfaces. The increased surface area (accessibility) and electrical conductivity of the composite result in significant enhancement in the capacity, cycling stability, and rate capability than the native Co3O4 phase.
Keywords: Cobalt oxide; Energy storage; graphene; lithium-ion batteries; Nanocomposites